Neutrophil and lymphocyte response to vitamins C and E supplementation in young calves - Pruiett, S.D.; Morrill, J.L.; Blecha, Frank; Higgins, James J.; Anderson, N.V.; Reddy, P.G. (Kansas Agricultural Experiment Station, 2012)
Calves were bottle-fed milk replacers at 10% of weekly adjusted body weight for 8 wk. Treatments were 1) no supplements (control), 2) .16 oz vitamin C, or 3) .16 oz vitamin C plus 125 IU/lb vitamin E. Lymphocytes and neutrophils isolated from day 14 and day 28 blood samples were assayed for neutrophil-mediated S. aureus phagocytosis and antibody-dependent cellular cytotoxicity, and for mitogen induced lymphocyte proliferation. Eye and nasal discharges of calves supplemented with vitamin C and vitamins C plus E were less than those of control calves for wk 1 to 8. Lymphocyte proliferation with the mitogens showed a trend for higher responses at wk 2 in vitamin C plus E supplemented calves. Neutrophils of calves supplemented with vitamin C showed decreased phagocytosis and lysis functions compared to those of control calves at wk 2 and 4. Neutrophil function of calves supplemented with vitamins C plus E was near or slightly higher than that of controls at wk 2 and 4, suggesting that the addition of vitamin E negated the adverse effects that vitamin C alone had on neutrophil functions.
The 1989 Annual KSU Dairy Day is known as Dairy Day, 1989
Keywords: Dairy; Neutrophil; Lymphocyte; Vitamin C; Vitamin E